Egalitarianism in the Qur'an: Dialectics of Concept and Reality - Latif, Hamdiah (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
The issue of equity and equality between men and women is one of the most serious problems and challenges that Muslims have faced in the modern era. Islam and Muslims are not only challenged to prove that their doctrine, as mentioned in the Qur’an and Sunnah, shows that egalitarianism is their main value, but they also should prove it in real life. However, it must be demonstrated not only through normative means as mentioned in its doctrine or history, but also by answering many contemporary challenges to the concept of equality between men and women today. This article examines the concept of egalitarianism from an Islamic perspective as found in the Qur'an.By using library research methods, it examines the further meaning of egalitarianism from an Al-Qur'anic perspective.